K-Band Centralized Cost-Effective All-Optical Sensing Signal Distribution Network - Maged Abdullah Esmail; Amr Ragheb; Hussein Seleem; Habib Fathallah; Saleh Alshebeili (IEEE Photonics Journal)
In this work, we propose and experimentally demonstrate a centralized all-optical network for sensing signal distribution to a large number of remote sites. The reach range of high-resolution sensing systems is often limited due to atmospheric effects. Employing a centralized optical fiber network for signal distribution to different nodes increases the effective reach distance, decreases the power consumption, and reduces the overall cost of the sensing system. The proposed centralized all-optical network is structured such that it has an all-optical wavelength converter hosted at a central office to guide a sensing signal to a specific site/sensor. This system enables using shared equipment in the transmitter which in turn reduces the overall cost of the network. The performance of the proposed system is investigated by transmitting a radar signal over various transmission media, i.e. fiber, free space optic (FSO), and hybrid fiber/FSO. Some empirical formulas for the signal power and dynamic range (DR) are derived. The results show that although optical signal switching introduces a penalty of 2.5-dB in the signal (DR), the signal still preserves its good shape and spectrum quality. In addition, the experimental results show the system performance with respect to target detection and range estimation.